Impact of frequency of application on the long-term efficacy of the biocontrol product Aflasafe in reducing aflatoxin contamination in maize - Atehnkeng, J.; Ojiambo, P.; Ortega Beltran, A.; Augusto, J.; Cotty, P.J.; Bandyopadhyay, R. (Frontiers Media, 2022)
Aflatoxins, produced by several Aspergillus section Flavi species in various crops, are a significant public health risk and a barrier to trade and development. In sub-Saharan Africa, maize and groundnut are particularly vulnerable to aflatoxin contamination. Aflasafe, a registered aflatoxin biocontrol product, utilizes atoxigenic A. flavus genotypes native to Nigeria to displace aflatoxin producers and mitigate aflatoxin contamination. Aflasafe was evaluated in farmers’ fields for 3 years, under various regimens, to quantify carry-over of the biocontrol active ingredient genotypes. Nine maize fields were each treated either continuously for 3 years, the first two successive years, in year 1 and year 3, or once during the first year. For each treated field, a nearby untreated field was monitored. Aflatoxins were quantified in grain at harvest and after simulated poor storage. Biocontrol efficacy and frequencies of the active ingredient genotypes decreased in the absence of annual treatment. Maize treated consecutively for 2 or 3 years had significantly (p < 0.05) less aflatoxin (92% less) in grain at harvest than untreated maize. Maize grain from treated fields subjected to simulated poor storage had significantly less (p < 0.05) aflatoxin than grain from untreated fields, regardless of application regimen. Active ingredients occurred at higher frequencies in soil and grain from treated fields than from untreated fields. The incidence of active ingredients recovered in soil was significantly correlated (r = 0.898; p < 0.001) with the incidence of active ingredients in grain, which in turn was also significantly correlated (r = −0.621, p = 0.02) with aflatoxin concentration. Although there were carryover effects, caution should be taken when drawing recommendations about discontinuing biocontrol use. Cost–benefit analyses of single season and carry-over influences are needed to optimize use by communities of smallholder farmers in sub-Saharan Africa.